The efficacy and safety of tofacitinib in Asian patients with moderate to severe chronic plaque psoriasis: A Phase 3, randomized, double-blind, placebo-controlled study. Issue 1 (October 2017) - Zhang, JianZhong; Tsai, Tsen-Fang; Lee, Min-Geol; Zheng, Min; Wang, Gang; Jin, HongZhong; Gu, Jun; Li, RuoYu; Liu, QuanZhong; Chen, Jin; Tu, CaiXia; Qi, ChunMei; et al.
Highlights: Tofacitinib is an oral Janus kinase inhibitor. Tofacitinib showed superior efficacy vs placebo in Asian patients with psoriasis. No unexpected safety findings were observed in Asian patients vs global studies. Abstract: Background: Tofacitinib is an oral Janus kinase inhibitor. Objective: This study assessed tofacitinib efficacy and safety vs placebo in Asian patients with moderate to severe chronic plaque psoriasis. Methods: Patients from China mainland, Taiwan, and Korea were randomized 2:2:1:1 to tofacitinib 5 mg (N = 88), tofacitinib 10 mg (N = 90), placebo → 5 mg (N = 44), or placebo → 10 mg (N = 44), twice daily (BID) for 52 weeks. Placebo-treated patients advanced to tofacitinib at Week 16. Co-primary efficacy endpoints: proportions of patients achieving Physician's Global Assessment (PGA) response ('clear' or 'almost clear') and proportion achieving ≥75% reduction from baseline Psoriasis Area and Severity Index (PASI75) at Week 16. Results: At Week 16, more patients achieved PGA and PASI75 responses with tofacitinib 5 mg (52.3%; 54.6%) and 10 mg (75.6%; 81.1%) BID vs placebo (19.3%; 12.5%; all p < 0.0001). Of patients with a Week 16 response, 73.6% and 75.0% maintained PGA response, and 76.8% and 84.9% maintained PASI75 to Week 52 with tofacitinib 5 mg and 10 mg BID, respectively. Over 52 weeks, 2.2–4.5% of patients across treatment groups experienced serious adverse events, and 1.1–6.8% discontinued due to adverse events. Conclusion: Tofacitinib demonstrated efficacy vs placebo at Week 16 in Asian patients with moderate to severe plaque psoriasis; efficacy was maintained through Week 52. No unexpected safety findings were observed. [NCT01815424]